Health Education Model for Elderly Hypertension on Knowledge, Attitudes, and Adherence to Following the Dietary Approaches to Stop Hypertension (DASH) - Reni Prima Gusty (Universitas Aisyah Pringsewu, 2023)
Applying the DASH diet to people with hypertension can reduce blood pressure. However, the existing phenomenon shows a low adherence to this diet. Appropriate methods of providing education are still needed as an effort to increase knowledge, attitudes, and dietary adherence. The study aimed to determine the effectiveness of educating elderly hypertensives models on knowledge, attitudes, and adherence to DASH (Dietary Approaches to Stop Hypertension) in community health centers. The study was a quasi-experimental design with one group pre-test and post-test, using purposive sampling with a sample of 40 people. The intervention had for two weeks. Collecting data using guided interviews with questionnaires that included socio-demographic characteristics, knowledge, attitudes, and adherence to the DASH diet. Statistical analysis using statistical paired sample t-test, Wilcoxon rank, and McNemar tests. The average age of the respondents was 62.62 years. Most of the women were unemployed, had hypertension less than 5 years, and had a family history of hypertension. After the health education intervention, there was an increase in knowledge (p= 0.000), attitude (p= 0.000), and adherence to the DASH diet (p= 0.000) with p less than 0.05. The elderly hypertensive health education model is effective in increasing the knowledge, attitudes, and adherence of elderly hypertensive patients to the DASH diet. It takes the support of families and health workers to achieve optimal DASH dietary adherence. Abstrak: Penerapan diet DASH pada penderita hipertensi mampu menurunkan tekanan darah. Namun fenomena yang ada menunjukkan rendahnya perilaku patuh melaksanakan diet ini. Metode pemberian pendidikan yang tepat masih diperlukan sebagai upaya meningkatkan pengetahuan,sikap dan kepatuhan diet. Tujuan studi untuk mengetahui efektifitas model pemberian edukasi pada lansia hipertensi terhadap pengetahuan, sikap dan kepatuhan menjalankan DASH ((Dietary Approaches to Stop Hypertension) di pusat kesehatan masyarakat. Penelitian ini merupakan penelitian eksperimen semu dengan rancangan control group pre- post test, menggunakan purposive sampling dengan jumlah sampel 40 orang. Intervensi dilakukan selama 2 minggu. Pengumpulan data menggunakan wawancara terpandu dengan kuesioner yang mencakup karakteristik sosio-demografis, pengetahuan, sikap, dan kepatuhan terhadap diet DASH. Analisis statistik menggunakan uji statistik paired sample t-test, uji peringkat Wilcoxon, dan uji McNemar. Rata-rata umur responden 62,62 tahun, Sebagian besar Wanita,tidak bekerja,mengalami hipertensi kurang dari 5 tahun dan memiliki Riwayat keluarga hipertensi. Setelah dilakukan intervensi pendidikan kesehatan terjadi peningkatan pengetahuan (p=0,000), sikap (p=0,000) dan kepatuhan (p=0,000) melakukan diet DASH dengan nilai p kurang dari 0,05. Model pendidikan lansia hipertensi efektif meningkatkan pengetahuan, sikap dan kepatuhan penderita lansia hipertensi untuk melakukan diet DASH. Dibutuhkan dukungan keluarga dan petugas kesehatan untuk mencapai kepatuhan diet DASH yang optimal